The Relationship Between Knowledge of Anemia and Compliance in Taking Iron Supplements in Adolescent Girls at the Bonepantai Community Health Center - Meilan Usman; Raden Maria Veronika Widiatrilupi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Anemia is a public health problem among adolescent girls in Indonesia, with a prevalence reaching 32%. Iron supplementation programs have been implemented, but compliance remains low. Knowledge about anemia is thought to influence adherence to iron supplementation. Objective: To analyze the relationship between knowledge about anemia and compliance in consuming iron tablets in adolescent girls at the Bonepantai Community Health Center. Methods: This quantitative study with a cross-sectional design involved 30 adolescent girls aged 12-19 years selected by purposive sampling. Data were collected using a structured questionnaire covering knowledge about anemia and adherence to iron supplement consumption. Data were analyzed using univariate and bivariate analysis with the Chi-Square test at a significance level of α = 0.05. Results: The majority of respondents were aged 15-17 years (50.0%) and had a high school education (60.0%). The level of knowledge was good at 43.3%, sufficient at 33.3%, and poor at 23.4%. Compliance with iron supplement consumption was 46.7% and non-compliance at 53.3%. The results of the Chi-Square test showed a significant relationship between knowledge about anemia and iron supplement compliance (p=0.013; χ²=8.742). Respondents with good knowledge had higher compliance (76.9%) compared to respondents with poor knowledge (14.3%). Conclusion: There is a significant relationship between knowledge about anemia and adherence to iron supplementation in adolescent girls. Intensifying comprehensive and sustainable health education programs is needed to improve knowledge and adherence to iron supplementation as an effort to prevent anemia.